The economic ramifications of liver cancer on a global, regional, and national scale - Yu, Jie; Chen, Qiaoyi; Ma, Jin (Frontiers in Medicine, 2025)
BackgroundA comprehension of the macroeconomic losses on a worldwide, regional, and national scale attributable to liver cancer is crucial for the optimal distribution of medical and research materials. The authors conducted an investigation into the macroeconomic impacts of the strain imposed by liver cancer in 2021 across 185 nations.MethodsThe data pertaining to disability-adjusted life years (DALY) for liver cancer and its associated risk factors were sourced from the 2021 records of the Global Burden of Disease investigation. Information pertaining to GDP, modified for purchasing power parity (PPP), originated from the World Bank; the integration of GDP and DALY data facilitated the estimation of macroeconomic losses through the application of a value of lost welfare (VLW) methodology. Every finding is articulated in 2021 international US dollars, calibrated for PPP.OutcomesIn the year 2021, the VLW resulting from liver cancer worldwide amounted to $141.95 B, representing 0.15% of the worldwide GDP. The worldwide VLW/GDP ratio for alcohol-related liver cancer was 0.033% (VLW = $31.835 B) Hepatitis B-associated liver cancer prevalence was 0.041% (VLW = $38.667 B) Hepatitis C-associated liver cancer prevalence was 0.056% (VLW = $53.268 B) incidence of NASH-related liver cancer was 0.012% (VLW = $11.653 B) the incidence of liver cancer attributed to alternative factors was recorded at 0.007% (VLW = $6.728 B). The East Asia, Southeast Asia, and Oceania super-region recorded the greatest VLW/GDP for liver cancer overall was 0.19%, with VLW of $39.08 B, the high-income super-region accounted for the second (VLW/GDP = 0.16%; VLW = $88.00 B).ConclusionThe global macroeconomic burden attributable to liver cancer is substantial, with far-reaching implications for productivity losses and healthcare expenditure. These evidence-based economic estimates provide a compelling rationale for strategic resource allocation towards liver cancer control programs.